Ethical aspects of researching subjective experiences in early-stage dementia - Pesonen, Hanna-Mari (Nursing ethics, 2011)
This article is based on a qualitative longitudinal study that followed the subjective experiences of both people living with dementia and their family members during the early stages of the illness. The purpose of this article is to describe and reflect on the ethical and methodological issues that occurred during data collection. The article focuses on the situation of the person with dementia and the family member and the role of the researcher when conducting the research interviews. Based on the results of this study, conducting research interviews with people with dementia and their family members poses several ethical and methodological challenges that must be addressed. In doing so, ethically sound dementia-specific research methods will be actively developed enhancing our understanding of living with dementia and providing new insights into the care of people with dementia and their family members.